Dampak Penerapan Teknologi Video Assistant Referee (VAR) dalam Sepak Bola - Yeremias Budi Irawan; Amelia Setiawan; Hamfri Djajadikerta (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2025)
This study examines the impact of implementing Video Assistant Referee (VAR) technology in football through a systematic literature review covering journals, books, research reports, and online articles. The analysis focuses on publications from the last five years ( from accredited international and national journals. Literature selection was conducted to ensure that only studies relevant to VAR in the context of professional football were analyzed. The results show that VAR improves the fairness and accuracy of referee decisions, especially in reducing fouls, offsides, and bias against the home team. This technology strengthens the integrity of the match, although there is still criticism that the length of the review slows down the rhythm of the game. From a business perspective, VAR has a positive impact on increasing club and league revenues through broadcasting rights, tickets, and merchandise, as well as attracting new sponsors by strengthening the image of professionalism in the competition. This study provides practical recommendations for league organizers in implementing VAR consistently and efficiently. Technological innovations such as semi-automated offside technology (SAOT) and artificial intelligence (AI) are projected to speed up the review process and increase transparency, supporting the growth of a fairer and more competitive modern football.